Resposta :
❒ Alternativa correta ''A''
--
Explicação passo-a-passo :
--
- Para resolver essa expressão, basta substituir a letra pelo número e multiplicar por ( -3 )
--
Resolução :
--
Para x = -3
[tex] \\ { \large \displaystyle \sf {x {}^{2} - 3x = }}[/tex]
[tex]{ \large \displaystyle \sf { - 3 {}^{2} - 3 \cdot( - 3) = }}[/tex]
[tex]{ \large \displaystyle \sf { - 9 -( -9) = }}[/tex]
[tex]{ \large \displaystyle \sf { - 9 + 9 = }}[/tex]
[tex]{ \green{ \boxed{ \boxed{ \pink{{ \large \displaystyle \sf { \: \: 0 \: \: }}}}}}} \\ \\ [/tex]
Resposta :
[tex] \\ { \green{ \boxed{ \boxed{ \pink{{ \large \displaystyle \sf { \: \: 0 \: \: }}}}}}} \\ [/tex]